2007
DOI: 10.1080/00754170701437096
|View full text |Cite
|
Sign up to set email alerts
|

Mother – infant group psychotherapy as an intensive treatment in early interaction among mothers with substance abuse problems

Abstract: In this article we present a novel method of outpatient care: brief, dynamic mother-infant group psychotherapy with mothers who have substance use problems. In this therapy, substance abuse treatment is part of mental health and parenting interventions. The focus is on preventing disturbance in the mother-infant relationship in this high-risk group. The clinical material is taken from 16 motherinfant dyads from six psychotherapy groups, which met weekly over six months from pregnancy to postpartum. The therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Mothers' negative prenatal expectations of their motherhood may indicate a lack of sufficient maternal attachment and protectiveness toward the baby. On the other hand, excessively high expectations of one's own motherhood may depict the role assigned to the child as that of a savior of one's whole life as typically described among drug‐abusing mothers (e.g., Belt & Punamäki, 2007). When this idealization is shattered by the reality of a very needy and dependent little baby, the nonintegrated, painful childhood memories may be activated in the mother.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mothers' negative prenatal expectations of their motherhood may indicate a lack of sufficient maternal attachment and protectiveness toward the baby. On the other hand, excessively high expectations of one's own motherhood may depict the role assigned to the child as that of a savior of one's whole life as typically described among drug‐abusing mothers (e.g., Belt & Punamäki, 2007). When this idealization is shattered by the reality of a very needy and dependent little baby, the nonintegrated, painful childhood memories may be activated in the mother.…”
Section: Discussionmentioning
confidence: 99%
“…Our results add to previous findings (Belt et al, 2011 ; Belt & Punamäki, 2007) of the use of mother–infant PGT among drug‐abusing mothers, and suggest that this treatment may help these high‐risk mothers to build and maintain a more positive view of the infant. Our results also show that in the course of successful PGT, the representation of one's own mother‐as‐mother also may change more positively and persist after the end of therapy, which would help the mother to more easily relate to her child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treating SA without addressing parenting leaves parents with insufficient skills for handling child behavior issues and makes them more vulnerable to drug relapse as a coping mechanism (Belt & Punamäki, 2007; Suchman et al, 2008; Whiteside-Mansell et al, 1999). Additionally, addressing parenting without addressing SA is likely futile as effective parenting requires a significant amount of emotional-regulation and intrinsic motivation, both of which are incompatible with drug and withdrawal states (Robinson & Berridge, 2003; George et al, 2012).…”
Section: Pathways Of Influence Linking Substance Abuse and Child Maltmentioning
confidence: 99%
“…There is a call for treatment programs that not only identify and assess perinatal substance abusers but also motivate them to better prepare for motherhood. Research has shown that most substance‐abusing women are willing to accept professional help to find a new identity as a successful mother rather than as a drug addict as far as appropriate treatment alternatives are available (Belt & Punamäki, 2007; Luthar, Suchman, & Altomare, 2007). The perinatal period poses a challenge for providing effective intervention programs for mother–infant dyads because addicted mothers often have a limited “time of soul‐searching,” and the infants are at high risk for physical and emotional problems (Howell, Heiser, & Harrington, 1999; Tronick et al, 2005).…”
mentioning
confidence: 99%